AXL mediates the nuclear translocation of EGFR - Corrigan, Kelsey (My University, 2015)
Cetuximab is an anti-epidermal growth factor receptor (EGFR) monoclonal antibody that has shown efficacy in numerous cancer types. Clinical data suggests that patients whom initially respond to cetuximab eventually acquire resistance. Cetuximab resistance is mediated by EGFR nuclear translocation and Src family kinases (SFKs). Additionally, recent studies have identified a role for the TAM family of receptor tyrosine kinases (Tyro, AXL, and Mer) in tumor biology. This lab has demonstrated that AXL is an integral cause of acquired resistance to cetuximab. The overarching aim of this study is to examine the relationship between AXL and nuclear EGFR, as there is a pressing need to refine available therapeutic regimens for patients with cetuximab-resistance. Through in vitro and in vivo studies, we examined the role of AXL in mediating the nuclear translocation of EGFR. This study demonstrated that Axl mediates EGFR translocation to the nucleus. Collectively, these studies undercover AXL as a critical mediator of nuclear EGFR translocation and may guide future therapeutic studies to target nuclear EGFR.